Orbital integrals on the Lorentz space of curvature -1 - Kurusa Árpád (ARCHIV DER MATHEMATIK, 2000)
We present a rotation symmetric model in the Euclidean space for the Lorentzian of curvature -- 1 in which the Lorentzian spheres around all the points of an a priori fixed spacelike totalgeodesic are straightlines. Investigating the mean value operators in this model yields to various representations of functions by means of their integrals over Lorentzian spheres.